Sex-related differences in the efficacy of Baclofen enantiomers on self-administered alcohol in a binge drinking pattern and dopamine release in the core of the nucleus accumbens - Jeanblanc, Jérôme; Sauton, Pierre; Houdant, Charles; Fernandez Rodriguez, Sandra; de Sousa, Sofia Vilelas; Jeanblanc, Virginie; Bodeau, Sandra; Labat, Laurence; Soichot, Marion; Vorspan, Florence; Naassila, Mickael (Frontiers in Pharmacology, 2023)
Introduction: Clinical studies on the effectiveness of Baclofen in alcohol use disorder (AUD) yielded mixed results possibly because of differential effects of the enantiomers and sex-related differences. Here we examined the effect of the different Baclofen enantiomers on alcohol intake and on evoked dopamine release in the core of the nucleus accumbens (NAcc) in male and female Long Evans rats. Methods: Rats were trained to chronically self-administer 20% alcohol solution in daily binge drinking sessions and were treated with the different forms of Baclofen [RS(±), R(+) and S(−)]. The effects on the evoked dopamine release within the core of the nucleus accumbens were measured in brain slices from the same animals and the alcohol naïve animals using the fast scan cyclic voltammetry technique. Results: RS(±)-Baclofen reduced alcohol intake regardless of sex but more females were non-responders to the treatment. R(+)-Baclofen also reduced alcohol intake regardless of sex but females were less sensitive than males. S(−)-Baclofen did not have any effect on average but in some individuals, especially in the females, it did increase alcohol intake by at least 100%. There were no sex differences in Baclofen pharmacokinetic but a strong negative correlation was found in females with a paradoxical effect of increased alcohol intake with higher blood Baclofen concentration. Chronic alcohol intake reduced the sensitivity to the effect of Baclofen on evoked dopamine release and S(−)-Baclofen increased dopamine release specifically in females. Discussion: Our results demonstrate a sex-dependent effect of the different forms of Baclofen with no or negative effects (meaning an increase in alcohol self-administration) in subgroup of females that could be linked to a differential effect on dopamine release and should warrant future clinical studies on alcohol use disorder pharmacotherapy that will deeply analyze sex difference.